Peranan Pendapatan Usahatani Wortel Desa Kanreapia Kecamatan Tombolo Pao Kabupaten Gowa Sulawesi Selatan - Raisa, Daeva Mubarika; Nurdin, Fadilah; Isma, Aam Azatil; Pratama, Ahmad Aditya; Utami, Sri Wira (Tarjih : Agribusiness Development Journal, 2023)
The objective of this study is to determine the magnitude of money generated from carrot farming in the research area, as well as the impact of carrot farming income on the local economy. Based on the completed analysis, carrot cultivation in Kanreapia Village, Tombolo Pao District, Gowa Regency yields an average income of IDR 80,000,000 per hectare. The respondents incurred an average of IDR 6,810,000/ha in fixed expenditures. The respondents experienced an average variable cost of IDR 7,950,000 per hectare for cultivating carrots. The primary expenses are variable costs, encompassing the expenditures on seeds, pesticides, fertilizers, and labor (including land preparation, planting, and harvesting). Among these variable costs, the biggest expense is attributed to inorganic fertilizer, amounting to IDR 2,900,000. Conversely, the most economical expenses are known as fixed costs, including the mean devaluation amount of the equipment utilized by the participants. Tractors incur the highest equipment depreciation expenses, totaling IDR 2,000,000, while sprayers and scythes have the lowest costs, totaling IDR 80,000. The respondents experienced an average production cost of IDR 14,760,000 per acre. The farmers have an average income of IDR 65,240,000 per hectare by cultivating carrots. Based on the findings of this study, the mean income per hectare earned by carrot farmers in Kanreapia Village, Tombolo Pao District, Gowa Regency is reported.